Paradigma Ulumul Qur’an dalam Penguatan Manajemen Pendidikan Islam Berbasis Nilai - Songyanan, Afifudin; Sarnoto, Ahmad Zain (Indo-MathEdu Intellectuals Journal, 2026)
This article aims to analyse the Ulumul Qur'an paradigm as the basis for strengthening value-based Islamic Education Management (MPI). This study uses a qualitative approach with a library research method. The data sources are secondary data obtained from the Ulumul Qur'an book, thematic Qur'anic interpretations, Islamic education management books, and relevant scientific journal articles. The data collection technique was carried out through searching and documenting literature related to Qur'anic values and educational management practices. The data were analysed using content analysis through a process of data reduction, concept categorisation, and thematic interpretation. The results of the study show that Ulumul Qur'an not only functions as a normative-theological discipline but also has epistemological, axiological, and practical relevance in strengthening Islamic education management. Qur'anic values such as amanah, itqan, shura, 'adl, and mas'uliyyah play an important role in strengthening leadership, planning, decision-making, and quality evaluation of Islamic educational institutions. These findings confirm that the Ulumul Qur'an paradigm can be a conceptual foundation for the development of ethical and sustainable Islamic educational management.